Association of the Androgenetic Alopecia with Coronary Artery Disease: A Case Control Study - Rahul Kumar Sharma, Divya Sharma (International Journal of Innovative Research in Medical Science, 2017)
Skin is the largest vital protective organ of the body which acts as a mirror of systemic diseases. Androgenetic alopecia (AGA) is a genetically determined patterned alopecia which is linked to coronary artery disease (CAD) or coronary heart disease. A hospital based, observational case control study was carried out on patients attending cardiology outpatient clinic and medicine outpatient clinic during the study period of 6 months. Case group consisted of hundred males who were known cases of coronary artery disease (on the basis of coronoary angiogram) and fulfilled the inclusion and exclusion criteria. Age matched controls were taken from patients who visited general medicine OPD for some acute short lasting illness (patients without any renal dysfunction, diabetes or any other associated systemic disease as per history). AGA was found in 78% of cases and 52% of controls. There was statistically significant association between AGA and CAD (P < 0.001, diagnostic odds ratio was 3.273, 95% Confidence interval [CI], 1.77-6.05). The grades of AGA with involvement of vertex are more important than just the mere presence of androgenetic alopecia in predicting the risk of CAD.